THE CONTRIBUTION OF A RESISTANCE TRAINING PROGRAMME ON THE GRAB AND TRACK STARTS TECHNIQUES IN COMPETITIVE SWIMMING. (Fiep Bulletin - online, 2011)
The swimming start is generally known to be a significant component for success in competitive swimming, especially in the shorter sprint races. The purpose of this study was to establish the effectiveness of a resistance training programme, designed to improve the vertical jumping (VJ) ability on the grab and front-weighted track starts techniques and identify the relationship between performance in the VJ and swimming start techniques. Twenty male swimmers participated in this study (mean ± SD: 19.5 ± 2.8 years). Participants were randomly assigned to a control group (n = 10) or experimental group (n = 10), which trained three times a week for 12 weeks. The tests before and after training programme were composed of grab and front-weighted track swimming start techniques and a vertical countermovement jump. The data were obtained from video images assessed using a camera positioned in the sagittal plane of motion. It was observed in both swimming start techniques the resistance training seems to increase the horizontal water reach of the CG (rCGw) during the air trajectory and resulting velocity of the CG at the take off instant, as suggested reducing the time spent in flight (FT) and total start time (TT). Significant correlation coefficients were observed between the VJ and rCGw and between FT and VJ in both swimming start techniques. Therefore, it is possible to speculate that coaches should consider the inclusion of regular resistance training concomitant with training swimming starts techniques to retrain the changed neuromuscular properties.
Keywords: swimming start techniques; swimming; vertical jump